Analisis Kualitas Air Permukaan Sungai Gandong Bojonegoro - Anidah H Triwulandari; Okik Hendriyanto Cahyonugroho (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
One of the rivers in Bojonegoro Regency is the Gandong River where the surrounding community uses the Gandong River for irrigation of agricultural land, transportation facilities, and household activities. The decline in water quality along the river is caused by factors such as population density, waste from activities, and the use of rivers that are not in accordance with their uses. This study aims to determine the quality of surface water and determine how to control water pollution in Gandong River, Bojonegoro Regency. The purposive sampling method was used to determine the sampling location at two points, namely the upstream and downstream parts of the river. Data analysis uses a quantitative approach and describes the results of research observations which are then compared with water quality standards that have been determined based on PP No. 22 of 2021 concerning the Implementation of Environmental Protection and Management. The condition of the Gandong River water quality seen from the measurement results on the BOD parameter at point 1 and point 2, namely 6 mg/L and 7 mg/L, does not meet the quality standards. While the parameters TDS, TSS, pH, COD, DO, and Total Coliform still meet the quality standards. To control pollution in the Gondang River, a strategy of periodic inspection of river water quality is needed even though most river water quality parameters are still within the quality standards.